1981
DOI: 10.1111/j.1471-4159.1981.tb10818.x
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetics Affect the Cerebral Metabolic Response to Circulatory Catecholamines

Abstract: This study examined whether the effect of intravenous infusions of either epinephrine or norepinephrine on cerebral metabolic rate for oxygen (CMRO2) in the dog was modified by different anesthetics. Infusions of either epinephrine or norepinephrine at rates of 0.1-0.25 mu.kg-1.min-1 reversibly increased the CMRO2 by 17-23% during anesthesia with cyclopropane 20% and nitrous oxide 50% in oxygen, whereas infusions at rates of 0.1-25.0 micrograms.kg-1.min-1 had no effect in dogs anesthetized with other inhalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In groups I and II control CBF values were higher than values observed during surgical levels of anesthesia (CBF = 60-70 ml-100 g-'-min-'), 17 -19 but less than or equal to values during light anesthesia with N 2 O (60-70%) and halothane ( < 0.1%) in O, (CBF « 80-140 mMOO g-'-min-1 ) 18 -2 ' with this model. In previous studies high control CBF values during light anesthesia have not impaired subsequent determination of CBF, cerebral metabolic rate for oxygen, cerebral metabolites (ATP, lactate, pyruvate, phosphocreatine, etc.…”
Section: Discussionmentioning
confidence: 61%
“…In groups I and II control CBF values were higher than values observed during surgical levels of anesthesia (CBF = 60-70 ml-100 g-'-min-'), 17 -19 but less than or equal to values during light anesthesia with N 2 O (60-70%) and halothane ( < 0.1%) in O, (CBF « 80-140 mMOO g-'-min-1 ) 18 -2 ' with this model. In previous studies high control CBF values during light anesthesia have not impaired subsequent determination of CBF, cerebral metabolic rate for oxygen, cerebral metabolites (ATP, lactate, pyruvate, phosphocreatine, etc.…”
Section: Discussionmentioning
confidence: 61%
“…Within the 62 animal studies identified, the majority of cases measured CBF response to NE and other agents, utilizing: autoradiographic diffusible tracer technique, electromagnetic flow probe, freely diffusible tracers, thermal diffusion probe, clearance method, laser‐Doppler flow velocity, radioactive gas elimination, radioactive microsphere, flow transducer and flow meter, visual recording software, and two other methods. The animal models studied included baboons (3), 17‐19 cats (8), 20‐27 dogs (11), 28‐38 goats (3), 39‐41 pigs (12), 42‐53 sheep (1), 54 mice (1), 55 rabbits (5), 56‐60 rats (17) 61‐77 and one retrospective study 16 with dogs, cats, rats, and humans. The characteristics of the animal studies can be seen in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the models was heavily anesthetized, with only two studies where the animals were lightly sedated 40,42 and four studies where animals had no sedation or anesthetia 39,41,55,60 . A further four articles 27,38,44,70 had NE injected with another vasoactive substance, seven articles 20,23,27,52‐54,70 where the models had craniotomy, five articles 34,36,37,73,77 where models had explanted brains for the evaluation of vessel response, four articles 44‐47 where models were administered cardiopulmonary resuscitation (CPR) during NE injection, four articles 48,50,51,74 where models had a TBI, three articles 21,35,66 where some models had hypothermia, two articles 41,56 where models had a superior cervical sympathetic ganglionectomy, one article where models had bile duct ligations, 19 and one article where models had induced endotoxin shock 43 . Seventeen studies had NE administered at varying dose levels on healthy models 17,20,26,29,36,39,40,52‐54,59,63‐65,69,71,72 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations